Effect of food simulating liquids on surface hardness of two dental resin composites - Ghavam M.; Arami S.; Hasani Tabatabaie M.; Mirzaei M.; Kermanshah H.; Pahlavan A.; Yasini E.; Dehghan M. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: Decreasing the hardness of dental restorative composites after curing in oral environment can influence their clinical durability. The aim of this study was to evaluate the effect of food-simulating liquids such as 25%, 50%, 75 % ethanol and 50 % heptane on surface hardness of two composites - (Gradia and P60) after curing and immersing time of 24 hours and 7 days."nMaterials and Methods: 45 specimens of each composite were prepared in a stainless steel mold with 6 mm diameter and 2 mm depth. 5 specimens of each composite were tested for microhardness immediately after curing as the control group. The other specimens of each composite were randomly divided into eight groups. Each specimen was immersed in one of the following solutions 25%, 50%, 75 % ethanol and 50 % heptane for either 24 hours or 7 days. Then the specimens were taken out of the solutions and washed and dried and transferred to the refrigerator until performing the test. In standard conditions, surface microhardness of specimens was evaluated by the microhardness device based on Vickers. The data were analyzed by one way ANOVA 3 way ANOVA and Tukey Post Hoc tests. The level of significance was set at p<0.05."nResults: Surface hardness of P60 composite was higher than that of Gradia. An analysis of variance in gradia and p60 showed significant difference between the control and all the other groups (P<0.05) except the 25% ethanol (P=0.514). After 24 hours all the solutions had significant effect on Gradia (P<0.05) except 50% and 75% ethanol (P=0.793). After 7 days all the solutions had significant effect on Gradia except 50% and 25% ethanol (P=0.385)and 50% and 75% ethanol (P=0.150) According to P60 after both 24 hours and 7 days all the solutions had significant effect on the hardness. 50 % heptane increased the hardness (P=0.00). 75% ethanol significantly decreased the hardness (P=0.000) followed by 50% (P=0.001) and 25% ethanol (P=0.007)."nConclusion: Based on the results of this study, the effect of time was not significant. P60 showed to be more resistant. 75% ethanol had much more effect followed by 50% and 25% ethanol. Heptane increased the mean surface hardness.